The Reform of Customs Regimes and the Chancay Megaport – A New Pacific Logistics Hub: A Case of Legal Reengineering - Cosio Jara, Edgar Fernando (Revista de Derecho, 2025)
At the end of 2024, the Chancay Multipurpose Port Terminal (hereinafter TPMP Chancay) was inaugurated with the participation of Chinese President Xi Jing Ping, managed by the company Cosco Shipping with Chinese and Peruvian capital. This megaport was established as the final destination of the so-called "New Silk Road" which would be traveled by post-Panamax ships that would leave mainly from the megaport of Shanghai in China, reducing the journey between Asia and America more than 10 days, turning Chancay into a hub port where most of the arrived cargo would be distributed to the rest of America and the world. This mega-project not only brought commercial and economic effects but also legal ones, insofar as customs controls in Chancay would not be limited to the traditional customs regimes of import and export but mainly to those of storage and transit, for the distribution of cargo to the rest of Latin America and to the export promotion regimes, so that Peru can benefit from this mega-project as a platform for the improvement of its exportable supply. In this article, the author analyzes the legal treatment of Customs Regimes in the face of the new scenario created by the Chancay TPMP and the modifications that had to be made to customs legislation to create the appropriate legal framework to make customs control viable without affectingthe commercial and economic operation of this work, in accordance with the principle of facilitation.
Keywords: Chancay; customs regimes; transit; warehouse; export